(untitled) (Nigerian Journal of Technology, 2018)
This work investigates the crash response of conical tubes made from different steel grades ranging from low to high strength steels using finite element (FE) simulations. The FE model was first validated against experimental results before being applied for the numerical analysis using LS DYNA software. Peak crushing load, mean load, energy absorption, crush force efficiency (CFE) and specific energy absorption (SEA) were evaluated from the cones of different steel grades and of various thicknesses. It was found that high strength steel exhibit high SEA and low CFE values. Both SEA and CFE were found to increase with increase in tube wall thickness for the five steel compared. For improved safety of the occupant, steel-CA5 is best because of higher CFE values for 1.5 mm, 2.0 mm and 2.5mm thicknesses. For better weight reduction, steel-DP600 with SEA of 10.6 kJ/kg is the best. Steel-HA3 and steel-SAP H440 with 2.5 mm thickness offer moderate CFE and SEA values. The findings of this study are useful in designing high safety performance vehicle front energy absorption components. http://dx.doi.org/10.4314/njt.v37i2.15